Pelatihan Literasi Media Kepada Mahasiswa Prodi. Ilmu Komunikasi Dalam Mewujudkan Smart City di Kota Kupang - Liliweri, 1Yohanes K.N. (Jurnal Pengabdian Kepada Masyarakat Undana, 2020)
The concept of a smart city (smart city) which is a big issue in big cities around the world encourages the active role and participation of the community in city management using a citizen centric approach so that there is a more dynamic and close interaction between citizens and service providers, in this case: Regional government. The target of this PKM activity is the college students of the FISIP Communication Studies program, Nusa Cendana University. This service was carried out due to college students' ignorance of the smart city program and the technology media used by the Kupang City Government. This PKM activity aims to create a community order with a creative-critical mindset and perspective. The community, especially youth (college students), will increasingly understand the benefits of media in the success of the smart city program. The material provided was in the form of the concept and application of the qlue smart city of Kupang City. The results of this PKM are that college students know about the city of Kupang smart city program complete with its qlue application, college students know the benefits of communication technology and the need for smart branding in the success of the smart city program. Keywords: Training, Media Literacy, College Students, Smart City Konsep kota cerdas (smart city) yang menjadi isu besar di kota-kota besar di seluruh dunia mendorong peran aktif dan partisipasi masyarakat dalam pengelolaan kota menggunakan pendekatan citizen centric sehingga terjadi interaksi yang lebih dinamis dan erat antara warga dengan penyedia layanan, dalam hal ini adalah Pemerintah Daerah. Adapun sasaran kegiatan PKM ini yakni Mahasiswa program Studi Ilmu Komunikasi FISIP Universitas Nusa Cendana. Pengabdian ini dilakukan karena ketidaktahuan mahasiswa akan program smart city serta media teknologi yang digunakan oleh Pemerintah Kota Kupang. Kegiatan PKM ini bertujuan untuk menciptakan tatanan masyarakat dengan pola pikir dan pandangan yang kritis-kreatif. Masyarakat terutama pemuda (mahasiswa) akan semakin paham akan manfaat media dalam mensukseskan program smart city. Materi yang diberikan berupa konsep dan aplikasi qlue smart city Kota Kupang. Hasil dari PKM ini yakni mahasiswa mengetahui adanya program smart city Kota Kupang lengkap dengan aplikasi qlue-nya, mahasiswa mengetahui manfaat teknologi komunikasi serta perlunya smart branding dalam mensukseskan program smart city. Kata Kunci: Pelatihan, Literasi Media , Mahasiswa, Smart City